« Lost… and found in translation » : la relation au monde dans The Missing Shade of Blue de Jennie Erdal (2012)Regards d’un traducteur sur sa pratique - Gilles ROBEL (E-REA)
The present article deals with the second novel by Scottish novelist Jennie Erdal (1951-2020), The Missing Shade of Blue (2012). Subtitled a « philosophical adventure », the novel focuses on a French translator who has come to Edinburgh to work on a translation of Scottish Enlightenment philosopher David Hume’s Essays. The author of the article is himself the author of a translation and critical edition of Hume’s Essays who knew Jennie Erdal and agreed to let her use his experience in the novel. Having now translated Jennie Erdal’s novel into French, as a practitioner and not as a theoretician of translation, he ponders on the nature of translation and the types of relations which are at the heart of the novel: the relationship between France and Scotland, between literature and philosophy, and he examines the paradoxical figure of the translator who usually is a shadowy, almost invisible character and finds himself thrust into the limelight as the narrator of the novel who relates and translates his thoughts and experiences of the connection between reality and fiction, between the author and its reader and between life and philosophy.